Reformulating communication strategy training to reduce topic fronting among TESL teachers in Malaysia - Megawati Soekarno; Irma Wani Othman; Ameiruel Azwan Ab Aziz; Nik Zaitun Nik Mohamed (Global Academic Excellence (M) Sdn Bhd, 2022)
Communication strategies involves the vast range of linguistic and paralinguistic techniques such as the use of negotiation of meaning to the very complex facial expressions. Despite being highly human based, the use of communication strategies needs to be learned and developed. The Malaysian classified variety, topic fronting, is a highly utilised communication strategy. However, despite being an achievement strategy, topic fronting does not abide by the English language grammatical rule. Although one of the primary factors of communication strategy is the independence from linguistic rules, a rampant use of this strategy among ESL learners might affect them adversely especially in academic discourse. This study looked into this strategy among the TESL practitioners from Universiti Malaysia Sabah. The findings obtained from their focus group discussions (FGD) identified four themes in the utilisation of topic fronting methods of overcoming it as well as the inculcation of suitable communication strategies. This study’s findings show that low utilisation of topic fronting should be able to allow the reformulation of the current communication strategy training.